Uncovering the Role of RNA-Binding Protein hnRNP K in B-Cell Lymphomas. (11th May 2019) - Gallardo, Miguel; Malaney, Prerna; Aitken, Marisa J L; Zhang, Xiaorui; Link, Todd M; Shah, Vrutant; Alybayev, Sanzhar; Wu, Meng-Han; Pageon, Laura R; Ma, Huaxian; Jacamo, Rodrigo; Yu, Li; et al.
Abstract: Background: Heterogeneous nuclear ribonucleoprotein K (hnRNP K) is an RNA-binding protein that is aberrantly expressed in cancers. We and others have previously shown that reduced hnRNP K expression downmodulates tumor-suppressive programs. However, overexpression of hnRNP K is the more commonly observed clinical phenomenon, yet its functional consequences and clinical significance remain unknown. Methods: Clinical implications of hnRNP K overexpression were examined through immunohistochemistry on samples from patients with diffuse large B-cell lymphoma who did not harbor MYC alterations (n = 75). A novel transgenic mouse model that overexpresses hnRNP K specifically in B cells was generated to directly examine the role of hnRNP K overexpression in mice (three transgenic lines). Molecular consequences of hnRNP K overexpression were determined through proteomics, formaldehyde-RNA-immunoprecipitation sequencing, and biochemical assays. Therapeutic response to BET-bromodomain inhibition in the context of hnRNP K overexpression was evaluated in vitro and in vivo (n = 3 per group). All statistical tests were two-sided. Results: hnRNP K is overexpressed in diffuse large B-cell lymphoma patients without MYC genomic alterations. This overexpression is associated with dismal overall survival and progression-free survival ( P < .001). Overexpression of hnRNP K in transgenic mice resulted in the development of lymphomas and reduced survival ( P < .001 for all transgenic lines; Line 171[n = 30]: hazard ratio [HR] = 64.23, 95% confidence interval [CI] = 26.1 to 158.0; Line 173 [n = 31]: HR = 25.27, 95% CI = 10.3 to 62.1; Line 177 [n = 25]: HR = 119.5, 95% CI = 42.7 to 334.2, compared with wild-type mice). Clinical samples, mouse models, global screening assays, and biochemical studies revealed that hnRNP K's oncogenic potential stems from its ability to posttranscriptionally and translationally regulate MYC . Consequently, Hnrnpk overexpression renders cells sensitive to BET-bromodomain-inhibition in both in vitro and transplantation models, which represents a strategy for mitigating hnRNP K-mediated c-Myc activation in patients. Conclusion: Our findings indicate that hnRNP K is a bona fide oncogene when overexpressed and represents a novel mechanism for c-Myc activation in the absence of MYC lesions.